Representasi Peran Keluarga Dalam Film Avatar 2 - HadiWijaya, Santo; Fauzi, Ahmad; Rofi Hidayah, Anis (Program Studi Ilmu Komunikasi, 2023)
Avatar 2 (Avatar: The Way of Water) is a film made by director James Cameron and this film is the second sequel to the first Avatar released in 2009. This film tells how Jake Sully and his family are targeted by Colonel Miles Quaritch. Jake Sully, who is also the leader of the Omatikaya tribe, puts Jake Sully in a pinch when he has to protect all members of the tribe and their families. The focus of the research problem is how to represent the role of the family in the film Avatar 2. The aim is to find out the representation of the role of the family in the film Avatar 2. By using a qualitative research method with a descriptive approach. Observation data collection and documentation with analysis of data reduction, data presentation, data verification and Charles Sanders Pierce's semiotic theory. The results of this research are: As a patriarchal family, this film describes a consensual type family. Parents educate the attitude of discipline, responsibility and can perform their potential skills. The father's role is to be a role model for his family members. Father is a good listener and a motivator. The role of older siblings is educated parents to have a sense of responsibility and confidence. This film adheres to several types of families depending on conditions, such as being democratic or authoritarian. On the other hand, there are also pluralistic and laissez faire or mixed characteristics.